(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the distinctive value system of Uzbek brides, emphasizing how traditional customs, familial roles, religious principles, and evolving societal norms shape their experiences. Utilizing a qualitative methodology, the study examines key aspects such as early marriage expectations, integration into extended families, preservation of cultural traditions, adherence to gender roles, and the influence of Islamic ethics. The findings highlight the complex interplay between enduring cultural practices and contemporary challenges faced by Uzbek brides in a rapidly modernizing society.​